Determinants of sudden cardiac death after heart transplantation. (25th November 2020) - Bonnet, G; Coutance, G; Waldmann, V; Aubert, O; Asselin, A; Raynaud, M; Racape, M; Bories, M.C; Varnous, S; Bruneval, P; Leprince, P; Marijon, E; et al.
Abstract: Background: Heart transplant recipients are at high-risk of sudden cardiac death (SCD). However, risk factors of SCD in heart recipients remained poorly described. Objective: To assess the predictors of SCD beyond the first-year post-transplant. Methods: We enrolled consecutive patients transplanted between 2004 and 2017 in two French referral centers. We excluded patients deceased during the first year. Patients underwent an evaluation at the day of transplantation and during the first year, comprising clinical, biological, histological, immunological (circulating anti-HLA DSA) and interventional (cardiac allograft vasculopathy assessment) parameters. Echocardiographies were routinely performed in all included patients according to a prespecified protocol. According to the last consensus, SCD was defined as an unexpected out-of-hospital cardiac arrest without obvious non-cardiac cause, in the first hour after initiation of symptoms. Cox model analysis was used to determine the parameters associated with sudden death risk. Results: A total of 913 patients were included. The median follow-up post-HT was 5.9 years (IQR=2.9–8.5). Among the 213 deaths after one year, 44 patients (21%) died from SCD. In this population, the incidence rate of SCD was 0, 82 per 100 person-year (95% CI: 0, 51–2, 05). Among the 60 parameters tested in univariate analysis, we identified 2 independent factors of sudden death after 1 year post-HT: left ventricular ejection fraction (LVEF) ≤55% any time after transplantation ( HR 4.07, 95% CI 1.94–8.53, p<0.001) and the presence of circulating anti-HLA DSA at the time of transplantation (HR 2.79, 95% CI 1.37–5.68, p=0.005). The incidence rate of SCD was 2.17 per 100 person-year (95% CI: 1.42; 4.60) and 1.21 per 100 person-year (95% CI: 0.80; 2.58) in patients with FEVG<55% (n=73) and in patients with pre-formed DSA (n=260), respectively. Conclusion: In a large multicentric and highly phenotyped cohort of heart transplant recipients, we identified two independent factors associated with SCD beyond the first year. This study provides fresh evidence of SCD assessment for improving risk stratification of HT recipients. Funding Acknowledgement: Type of funding source: None